2011
DOI: 10.1021/om200642s
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Palladium(II) Complexes for CO/Vinyl Arene Copolymerization in the Presence of Carbon Dioxide

Abstract: New dicationic and monocationic palladium complexes with 2,2'-bipyridine ligands bearing perfluorinated ponytails have been prepared and used as catalysts for CO/4-tert-butylstyrene (TBS) and CO/styrene (ST) copolymerization in supercritical carbon dioxide (scCO2) and in CO2-expanded liquids. Best catalytic performances were achieved carrying out the copolymerization in carbon dioxide expanded substrates in the presence of 2,2,2-trifluoroethanol (TFE). The dicationic systems with 5,5’-substituted ligands [Pd(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…In addition to that, to the best of our knowledge, there are no reports on Ru(II)‐based OEC decorated with perfluorocarbon (PFC) pendants, there exists only a few reports on metal complexes bearing fluorous tails, and even fewer structural studies on metal complexes having pyridine‐based ligands . This is probably due to the difficulties in crystallizing compounds with long fluorous tails (vide infra).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, to the best of our knowledge, there are no reports on Ru(II)‐based OEC decorated with perfluorocarbon (PFC) pendants, there exists only a few reports on metal complexes bearing fluorous tails, and even fewer structural studies on metal complexes having pyridine‐based ligands . This is probably due to the difficulties in crystallizing compounds with long fluorous tails (vide infra).…”
Section: Introductionmentioning
confidence: 99%
“…16) is summarized in Table 9. The Δ 15N coord obtained upon Rh(I) complexation of 1-methylpyrazole (143) and analogous imidazole (144) suggest metal coordination at position N2 (À79.3 ppm) and N3 (À64.6 ppm), respectively [103]. For the octahedral cationic Ir(III) (145) and Ru(III) (146) complexes of three coordinated pyrazoles in acetoned 6 , N2-coordination was shown by Otting and coworkers [97].…”
mentioning
confidence: 88%
“…In an investigation of the potential use of cationic palladium complexes with bidentate N-N perfluorinated 2,2 0 -bipyridine ligands as catalysts in carbon monoxide/α-olefin copolymerization processes [144] HOESY for the PF 6 À along with diffusion NMR studies indicated that BArF À does not coordinate, whereas the OTs À and PF 6 À tightly interact with the cation. The complex encompassing the non-coordinating BArF À shows the most shielded pyridinyl nitrogens and the largest jΔ 15N coord j (Table 18), whereas those with OTs À and PF 6 À counterions showed a significant deshielding, due to tight ion pairing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…56 The CO/vinyl arene copolymerization was catalysed by cationic Pd(II) complexes in the presence of CO 2 . 57 Silacarboxylic acids were found to be efficient CO releasing molecules in Pd-catalyzed carbonylation reactions. 58 The efficient copolymerizations of methylacrylate with CO and ethylene with norbornene were reported, catalysed by a Pd-phosphinosulfonate system [o-(o-MeOC 6 H 4 ) 2 P)C 6 H 4-SO 3 ].…”
Section: Organometallic Chemistrymentioning
confidence: 99%